The Impact of the Fuzzy Delphi Technique on Technology Methods Based on Design Thinking - Daud, Anshar; Sitio, Sartika Lina Mulani; Bakri, Asri Ady; Judijanto, Loso; Ridwan (Journal of Education Technology, 2024)
As technology becomes important in people's lives, there is a call to integrate technology into education. Therefore, this research aims to look at the elements needed to integrate technology as a learning platform based on design thinking. This research is quantitative research using the Fuzzy Delphi technique. The approach used to collect research data is to use a questionnaire instrument. The number of experts involved was 18 people, 8 people from the field of education, 5 people from educational technology, and 5 people from design thinking. The research results show that the eight elements are accepted by experts with a consensus percentage above 75% with a threshold value (d) ≤ 0.2. The conclusions of these eight elements are using technology or the internet, choosing technological tools or resources, assessing the credibility and relevance of sources, using technology to analyze information, using technology to support teamwork, using technology to help students share information, utilizing technology to monitor assignments, utilizing technology to interact directly with experts is necessary for integrating technology as a learning platform based on design thinking. This research implies that teachers and students have started to apply these eight elements in the classroom learning process.